MJM MedTalks (S02E04+05): Building Healthcare: How Architecture Influences Medicine - Renée-Claude Bider; Annmarie Adams; Masha Samuel; Vanessa Ross; Samy Amghar; Katherine Lan; Esther SH Kang; Khiran Arumugam; mer Talbo; Predrag Jovanovic; Jan Pack; Susan Joanne Wang (McGill Journal of Medicine)
The McGill Journal of Medicine (MJM) Podcast Series, MJM MedTalks, interviews members of the medical and health sciences community from McGill, and beyond to gain insights into their careers, research, advocacy, and more. This series aims to enhance knowledge sharing between experts and trainees in the medical field. In this episode, Renée-Claude Bider, a Master’s student in medical physics and Podcast Associate at the McGill Journal of Medicine, interviews Prof. Annmarie Adams, who is jointly appointed in McGill University's School of Architecture and the Department of Social Studies of Medicine. Dr. Annmarie Adams trained as an architect and architectural historian at UC Berkeley. Her research focuses on how medicine, gender, and architecture intersect. In the first part of their conversation, Bider and Prof. Adams discuss the history of hospital architecture, starting in the late 1800s and focusing on Montreal and Canadian institutions, including the Royal Victoria Hospital, Montreal Neurological Institute, Montreal General Hospital, The McGill University Health Centre (Montreal, Canada), Sick Kids (Toronto, Canada) and McMaster Children’s Hospital (Hamilton, Canada). In the second part of their conversation, Bider and Prof. Adams discuss the architecture of specialized healthcare spaces, such as long-term care homes, birthing suites, palliative care, and cancer centers. They end their conversation by discussing Prof. Adams' ongoing research into the life of influential physician Maude Abbott and advice for trainees in the medical field. A glossary of terms, a content overview, a list of relevant links and research articles, supplementary images from Prof. Adams’ collection, and a transcript of the interview are included in the show notes for this episode.